Taking meredith out of Grey's anatomy: automating hospital ICU emergency signaling - Ahmed, Tarem; Ahmed, Supriyo Shafkat; Chowdhury, Fazle Elahi (© 2016 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 41st IEEE International Conference on Acoustics, Speech and Signal Processing, ICASSP 2016 [© 2016 Institute of Electrical and Electronics Engineers Inc.] The conference paper's definite version is available at: http:// 10.1109/ICASSP.2016.7472004